Evaluacion del efecto nematicida de cepas de bacillus spp. - Marquez Gutierrez, M.E.=700 1 Torres Sanchez, L.A.; Escobar Hernandez, M.
(Es, En)
Ilus., 20 ref.
Keywords: BACILLUS LICHENIFORMIS; BACILLUS THURINGIENSIS; CONTROL BIOLOGICO; MELOIDOGYNE INCOGNITA; ENZIMAS; CUBA; BETA EXOTOXINA; DELTA ENDOTOXINA; ENZIMAS EXOCELULARES